The Diagnosis and Management of Vasovagal Syncope in Pediatric Patients - Zou, Runmei; Wang, Shuo; Wang, Cheng (Journal of Neurology and Epidemiology, 2022)
Vasovagal syncope is the most common cause of syncope in pediatric patients. The present study is aim to provide a comprehensive literature review of the latest advances in the diagnosis and treatment of vasovagal syncope in children. Diagnosis of vasovagal syncope is based on clinical history. For patients with suspected VVS but lack of confident diagnosis after initial assessment, head-up tilt test is helpful. There are four options for treatment of vasovagal syncope: conservative therapy, pharmacologic therapy, pacemaker therapy, and catheter ablation of ganglionated plexi. Conservative therapy (health education, avoidance of triggers, salts and water intake, physical countermeasures and orthostatic training) is recommended for patients with occasional syncope. Pharmacological therapy should be considered for patients with recurrent syncope or for whom conservative therapy has failed. Patients with the predominantly cardioinhibitory response, associated with repeated injury, limited prodromes, and documented asystole may benefit from cardiac pacing. Catheter ablation of ganglionated plexi is a new strategy, its efficacy and safety in pediatric patients should be verified by randomized controlled trials.